Multidisciplinary Approach to Cover an Apex-Exposed Tooth: A Case Report after 6-Year Follow-Up - Jamila Kissa; Wafa El Kholti; Khadija Sekak; Sihame Chemlali (Case Reports in Dentistry)
Introduction. The prognosis for a successful treatment of gingival recessions (GRs) is one of the main criteria for deciding whether or not and how to perform root coverage surgery. The defect-related factors are the most important to predict root coverage outcomes. Thus, severe GR could make the root coverage (RC) challenging especially in cases with advanced interdental clinical attachment loss (ICAL). Case Presentation. This case report demonstrates a challenging management of a deep localized Miller Class III GR with root apex exposure associated with ICAL. After initial therapy, the treatment had consisted of a multidisciplinary approach involving endodontic treatment, periodontal plastic surgery including a laterally positioned flap, and orthodontic treatment. The 6-year follow-up showed improvement in clinical outcomes (recession reduction (RR) and keratinized tissue (KT) augmentation) and a higher patient satisfaction. Conclusions. This case report demonstrates the role of the multidisciplinary approach in the management of deep GRs associated with ICAL. A rational choice of the RC technique was critical to achieve good clinical outcomes.